Perspectives of Phage–Eukaryotic Cell Interactions to Control Epstein–Barr Virus Infections - Górski, Andrzej; Międzybrodzki, Ryszard; Jończyk-Matysiak, Ewa; Weber-Dąbrowska, Beata; Bagińska, Natalia; Borysowski, Jan (Frontiers in Microbiology, 2018)
Recently, leading medical journals emphasized the importance of further studies on the potential application of bacterial viruses (phages) for the treatment of antibiotics-resistant infections outlining the present status of the therapy and perspectives for the future. Furthermore, a leading scientific journal pointed to the recent progress in research on phage interactions with eukaryotic cells (especially cells of the immune system) and potential implications of their results for our broader understanding of the role of phages – not only as „bacteria eaters” – but also as an important part of our body defense protecting against external and internal pathogenic invaders (as suggested previously, Górski, 2005). This illustrates how our understanding of the actual role and potential of phages is expanding and how worldwide interest in their use in medicine is growing. In this article we envision how this advancement of our knowledge about phages could be translated into the progress in combating herpesvirus infections especially those caused by Epstein-Barr virus (EBV).